Extracellular cAMP-Adenosine Pathway Signaling: A Potential Therapeutic Target in Chronic Inflammatory Airway Diseases - Pacini, Enio Setsuo Arakaki; Satori, Naiara Ayako; Jackson, Edwin Kerry; Godinho, Rosely Oliveira (Frontiers in Immunology, 2022)
Adenosine is a purine nucleoside that, via activation of distinct G protein-coupled receptors, modulates inflammation and immune responses. Under pathological conditions and in response to inflammatory stimuli, extracellular ATP is released from damaged cells and is metabolized to extracellular adenosine. However, studies over the past 30 years provide strong evidence for another source of extracellular adenosine, namely the “cAMP-adenosine pathway.” The cAMP-adenosine pathway is a biochemical mechanism mediated by ATP-binding cassette transporters that facilitate cAMP efflux and by specific ectoenzymes that convert cAMP to AMP (ecto-PDEs) and AMP to adenosine (ecto-nucleotidases such as CD73). Importantly, the cAMP-adenosine pathway is operative in many cell types, including those of the airways. In airways, β2-adrenoceptor agonists, which are used as bronchodilators for treatment of asthma and chronic respiratory diseases, stimulate cAMP efflux and thus trigger the extracellular cAMP-adenosine pathway leading to increased concentrations of extracellular adenosine in airways. In the airways, extracellular adenosine exerts pro-inflammatory effects and induces bronchoconstriction in patients with asthma and chronic obstructive pulmonary diseases. These considerations lead to the hypothesis that the cAMP-adenosine pathway attenuates the efficacy of β2-adrenoceptor agonists. Indeed, our recent findings support this view. In this mini-review, we will highlight the potential role of the extracellular cAMP-adenosine pathway in chronic respiratory inflammatory disorders, and we will explore how extracellular cAMP could interfere with the regulatory effects of intracellular cAMP on airway smooth muscle and innate immune cell function. Finally, we will discuss therapeutic possibilities targeting the extracellular cAMP-adenosine pathway for treatment of these respiratory diseases.